Late Permian High-Ti Basalt in Western Guangxi, SW China and Its Link With the Emeishan Large Igneous Province: Geochronological and Geochemical Perspectives - Zhang, Chenguang; Zeng, Renyu; Li, Changming; Jiang, Jian; Wang, Tianguo; Shi, Xingjun (Frontiers in Earth Science, 2021)
High-Ti (Ti/Y) flood basalts are widely distributed in the Late Permian Emeishan large igneous province (LIP), SW China, and their spatial distribution and genetic mechanism are important to reveal the role of plume-lithosphere interactions in the LIP origin. Western Guangxi is located on the eastern edge of Emeishan LIP. To explore the genesis of the high-Ti basalt in western Guangxi and any genetic link with the Emeishan LIP, we performed whole-rock geochemical and Sr-Nd isotope and zircon U-Pb-Hf isotope analyses on the Longlin basalts from western Guangxi. The results indicate that the Longlin basalt from Tongdeng area has relatively high SiO2 but low MgO and TFe2O3 contents. The rocks have zircon εHf(t) = −0.42 to 6.41, whole-rock (87Sr/86Sr)i = 0.707167–0.707345, and εNd(t) = −2.5 to −2.14. In contrast, the Longlin basalt from Zhoudong area has relatively low SiO2 but high MgO and TFe2O3 contents. The rocks have whole-rock (87Sr/86Sr)i = 0.706181–0.706191 and εNd(t) = −0.57 to 0.69. Four Longlin basalt samples display LREE enrichments and HREE depletions, and with indistinct δEu and δCe anomalies. LA-ICP-MS zircon U-Pb dating on three Longlin basalt samples (from different localities) yielded consistent weighted average age of 257.9 ± 2.6 Ma (MSWD = 0.55), 259.5 ± 0.75 Ma (MSWD = 3.0), and 256.7 ± 2.0 Ma (MSWD = 0.68), indicating a Late Permian emplacement. Considering the similar age and geochemical features between the Longlin basalt and Emeishan flood basalts, we interpret that the former is spatially, and temporally associated with the Emeishan LIP. Geochemical features show that the high-Ti basalts in western Guangxi resemble Deccan-type continental flood basalts (CFBs), which were derived by decompression melting of the mantle plume. Combined with previous geochemical studies, we suggest that the difference in Ti content and Ti/Y ratio in CFBs are related to the depth and melting degree of mantle source, in which high-Ti features may have been linked to low degree of partial melting in the deep mantle.